A "blue ocean" strategy for developing visitor wine experiences: Unlocking value in the Cape region tourism market. (June 2020) - Priilaid, David; Ballantyne, Roy; Packer, Jan
Abstract: The metaphor of "Blue Ocean" thinking is used to investigate visitors' preferences for "red ocean" and potential "blue ocean" wine experiences in South Africa's Cape region. A questionnaire was completed by 443 tourists who identified as wine tourists. "Red ocean" activities, e.g., wine estate bus tours were less attractive to tourists than potential "blue ocean" activities, e.g., paired wine and dinner tasting. Such activities are not commonly available at present and represent a significant opportunity. The paper shows how visitor research and fresh strategic thinking can unlock value in the tourism market.